Differences in Contraction-Induced Hemodynamics and Surface EMG in Duchenne Muscular Dystrophy (2016)
Duchenne muscular dystrophy (DMD) is the most common and devastating type of muscular dystrophy worldwide. In this study we have investigated the potential of the combined use of non-invasive near-infrared spectroscopy (NIRS) and surface electromyography (sEMG) to assess contraction-induced changes in oxygenation and myoelectrical activity, respectively in the biceps brachii of eight DMD patients aged 9–12 years and 11 age-matched healthy controls. Muscle tissue oxygenation index (TOI), oxyhemoglobin (HbO2), and sEMG signals were continuously measured during a sustained submaximal contraction of 60 % maximal voluntary isometric contraction, and post-exercise recovery period. Compared to controls, DMD subjects showed significantly smaller changes in TOI during the contraction. In addition, during the reoxygenation phase some dynamic parameters extracted from the HbO2 measurements were significantly different between the two groups, some of which were correlated with functional performances on a 6-min walking test. In conclusion, non-invasive continuous monitoring of skeletal muscle oxygenation by NIRS is feasible in young children, and significant differences in contraction-induced deoxygenation and reoxygenation patterns were observed between healthy controls and DMD children.